Genetic silencing of striatal CaV1.3 prevents and ameliorates levodopa dyskinesia - Steece‐Collier, Kathy (Mov Disord, 2019)
BACKGROUND: Levodopa‐induced dyskinesias are an often debilitating side effect of levodopa therapy in Parkinson's disease. Although up to 90% of individuals with PD develop this side effect, uniformly effective and well‐tolerated antidyskinetic treatment remains a significant unmet need. The pathognomonic loss of striatal dopamine in PD results in dysregulation and disinhibition of striatal CaV1.3 calcium channels, leading to synaptopathology that appears to be involved in levodopa‐induced dyskinesias. Although there are clinically available drugs that can inhibit CaV1.3 channels, they are not adequately potent and have only partial and transient impact on levodopa‐induced dyskinesias. METHODS: To provide unequivocal target validation, free of pharmacological limitations, we developed a CaV1.3 shRNA to provide high‐potency, target‐selective, mRNA‐level silencing of striatal CaV1.3 channels and examined its ability to impact levodopa‐induced dyskinesias in severely parkinsonian rats. RESULTS: We demonstrate that vector‐mediated silencing of striatal CaV1.3 expression in severely parkinsonian rats prior to the introduction of levodopa can uniformly and completely prevent induction of levodopa‐induced dyskinesias, and this antidyskinetic benefit persists long term and with high‐dose levodopa. In addition, this approach is capable of ameliorating preexisting severe levodopa‐induced dyskinesias. Importantly, motoric responses to low‐dose levodopa remained intact in the presence of striatal CaV1.3 silencing, indicating preservation of levodopa benefit without dyskinesia liability. DISCUSSION: The current data provide some of the most profound antidyskinetic benefit reported to date and suggest that genetic silencing of striatal CaV1.3 channels has the potential to transform treatment of individuals with PD by allowing maintenance of motor benefit of levodopa in the absence of the debilitating levodopa‐induced dyskinesia side effect. © 2019 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.